Comparitive Study of Single, Double and Multi Shell CNTMOSFET for Biosensing Applications (Journal of Pharmaceutical Negative Results, 2022)
It becomes very significance to sense and quantify the proteins in the fields of biotechnology. Among various other nano bio sensors, carbon based devices serves well in effective sensing applications. The sensed data can be quantified using a CNT based MOSFET. Carbon Nano Tube consists of multi shells, one inside another, contributes good conductance compared to Single-walled Carbon Nano. Each shell can have different chiralities depending on the direction they are rolled up and multiwalled are always metallic. Modelling and performance analysis of Multi-walled Carbon Nano Tube based devices are addressed less due to their complexity in both structure and characterization. In this paper, Multi-walled Carbon Nano Tube Field Effect Transistor is analytically modelled and simulated to study its electric performance characteristics with respect to Single, Double shells based samae device. Various device parameters viz., gate dielectric (k1), gate distance from the channel(h), number of channels(N), gate length(Lg) are varied, plotted and the corresponding capacitance responses are compared.